2007
DOI: 10.1111/j.1365-2559.2007.02797.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of p53 gene mutations and protein overexpression in localized gastrointestinal stromal tumours

Abstract: Alterations in p53 were more commonly observed in localized GISTs at higher risk of relapse. This suggests that they are significant as an independent, poor prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…We found mutations in 16.4% of cases, selected on the basis of p53 protein expression. In agreement with our results, Ryu et al showed TP53 mutations in 22% of the GISTs with high p53 protein expression (24). The low percentage of mutation in high p53 expressers might reflect its late occurrence in a subpopulation of cells, for which direct sequencing might not be able to identify it.…”
Section: Discussionsupporting
confidence: 81%
“…We found mutations in 16.4% of cases, selected on the basis of p53 protein expression. In agreement with our results, Ryu et al showed TP53 mutations in 22% of the GISTs with high p53 protein expression (24). The low percentage of mutation in high p53 expressers might reflect its late occurrence in a subpopulation of cells, for which direct sequencing might not be able to identify it.…”
Section: Discussionsupporting
confidence: 81%
“…Our meta-analysis showed that p53 expression appeared more often in recurred or metastasized GIST (malignant group) than in tumors with disease-free follow-up (benign group). Furthermore, p53 expression was significantly associated with the established prognostic criteria (NIH system), and was consistent with most previous GIST studies (6,(11)(12)(13)15,(16)(17)(18)(19). NIH I+H showed more positivity with p53 than NIH VL+L tumors.…”
Section: Discussionsupporting
confidence: 76%
“…A total of 19 publications met the inclusion criteria (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The studies by Chou et al, Padilla et al, Romeo et al and Kwon et al were excluded due to insufficient information to calculate an OR (25)(26)(27)(28), and the study by Sakurai et al was also excluded since they used telomerase activity as the criteria for measuring the malignant risk of GIST (29).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Larger series, however, have found both size and mitotic rate to be independent predictors. 19,28 This discrepancy may be explained by review of the hazard ratio as the hazard ratio for mitotic count >10/ 50HPF is high (HR 14.6-45.9) and is typically several fold larger than that for size >10 cm (HR 2.5-20.9). 19,29 Achieving R0 resection is vital as recurrent disease fails to be indefinitely controlled with tyrosine kinase inhibitors.…”
Section: Discussionmentioning
confidence: 94%